Direct and indirect impacts of climate change on microbial and biocrust communities alter the resistance of the N cycle in a semiarid grassland. (26th August 2014) - Delgado‐Baquerizo, Manuel; Maestre, Fernando T.; Escolar, Cristina; Gallardo, Antonio; Ochoa, Victoria; Gozalo, Beatriz; Prado‐Comesaña, Ana; Wardle, David
Summary Climate change will raise temperatures and modify precipitation patterns in drylands worldwide, affecting their structure and functioning. Despite the recognized importance of soil communities dominated by mosses, lichens and cyanobacteria (biocrusts) as a driver of nutrient cycling in drylands, little is known on how biocrusts will modulate the resistance (i.e., the amount of change caused by a disturbance) of the N cycle in response to climate change. Here, we evaluate how warming (ambient vs. ˜2.5 °C increase), rainfall exclusion (ambient vs. ˜30% reduction in total annual rainfall) and biocrust cover (incipient vs. well‐developed biocrusts) affect multiple variables linked to soil N availability (inorganic and organic N and potential net N mineralization rate) and its resistance to climate change during 4 years in a field experiment. We also evaluate how climate change‐induced modifications in biocrust and microbial communities indirectly affect such resistance. Biocrusts promoted the resistance of soil N availability regardless of the climatic conditions considered. However, the dynamics of N availability diverged progressively from their original conditions with warming and/or rainfall exclusion, as both treatments enhanced N availability and promoted the dominance of inorganic over organic N. In addition, the increase in fungal:bacterial ratio and the decrease in biocrust cover observed under warming had a negative indirect effect on the resistance of N cycle variables. Synthesis. Our results indicate that climate change will have negative direct and indirect (i.e. through changes in biocrust and microbial communities) impacts on the resistance of the N cycle in dryland soils. While biocrusts can play an important role slowing down the impacts of climate change on the N cycle due to their positive and continued effects on the resistance of multiple variables from the N cycle, such change will progressively alter N cycling in biocrust‐dominated ecosystems, enhancing both N availability and inorganic N dominance.